2009
DOI: 10.1371/journal.pone.0005891
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Crosstalk between Photoperiod and Temperature on the Heading-Date in Rice

Abstract: Photoperiod and temperature are two important environmental factors that influence the heading-date of rice. Although the influence of the photoperiod on heading has been extensively reported in rice, the molecular mechanism for the temperature control of heading remains unknown. This study reports an early heading mutant derived from tissue culture lines of rice and investigates the heading-date of wild type and mutant in different photoperiod and temperature treatments. The linkage analysis showed that the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 37 publications
1
54
0
8
Order By: Relevance
“…The heading-date of the mutant was almost identical under SD and LD conditions, while the heading-date of Zhonghua 11 was 21 d later under LD condition than SD condition [23]. This result suggested that the mutant was photoperiod-insensitive.…”
Section: The Heading Date Of Mutant and Wild Type In Different Regionsmentioning
confidence: 86%
See 3 more Smart Citations
“…The heading-date of the mutant was almost identical under SD and LD conditions, while the heading-date of Zhonghua 11 was 21 d later under LD condition than SD condition [23]. This result suggested that the mutant was photoperiod-insensitive.…”
Section: The Heading Date Of Mutant and Wild Type In Different Regionsmentioning
confidence: 86%
“…japonica, wild type) and lf1132, a mutant derived from a tissue culture line of Zhonghua 11. The mutant has a loss of function allele for the Hd1 gene, with two inserted fragments and several single-base substitutions at the Hd1 locus [23]. Plants were grown in the experimental field of the Tianjin Agricultural Academy of Science (TAAS), Tianjin Province and at Sanya, Hainan Province.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nishida et al (2001) menyatakan gen-gen yang paling berperan dalam pembungaan padi berada pada lokus Ef1, E, dan Se1. Penelitian lain menunjukkan QTL Hd1 merupakan turunan (downstream) dari QTL Hd3a yang menyebabkan padi lebih cepat berbunga pada kondisi hari pendek (Yano et al 2000, Yano et al 2001, Imaizumi and Kay 2006, Tamaki et al 2007, Izawa 2007, Komiya et al 2008, Luan et al 2009, Itoh et al 2010.…”
unclassified